2007
DOI: 10.1016/j.mrfmmm.2006.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenicity of cinnamaldehyde and vanillin in human cells: Global gene expression and possible role of DNA damage and repair

Abstract: Vanillin (VAN) and cinnamaldehyde (CIN) are dietary flavorings that exhibit antimutagenic activity against mutagen-induced and spontaneous mutations in bacteria. Although these compounds were antimutagenic against chromosomal mutations in mammalian cells, they have not been studied for antimutagenesis against spontaneous gene mutations in mammalian cells. Thus, we initiated studies with VAN and CIN in human mismatch repair-deficient (hMLH1 − ) HCT116 colon cancer cells, which exhibit high spontaneous mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 48 publications
0
38
0
1
Order By: Relevance
“…In the in vitro study of Kapiszewska et al (2005) ethanolic extract of Origanum heracleoticum showed no protective effect against H 2 O 2 -induced DNA damage in human lymphocytes. King et al (2007) observed significant levels of DNA damage in colon cancer cells treated with cinnamaldehyde after 4 h of exposure. Although DNA fragmentation seen in Comet Assay can also be a consequence of excision and repair, rather than necessarily being irreversible final damage, authors suggest that cinnamaldehyde acts as an antimutagen through the enhancement of recombinational repair.…”
Section: Discussionmentioning
confidence: 85%
“…In the in vitro study of Kapiszewska et al (2005) ethanolic extract of Origanum heracleoticum showed no protective effect against H 2 O 2 -induced DNA damage in human lymphocytes. King et al (2007) observed significant levels of DNA damage in colon cancer cells treated with cinnamaldehyde after 4 h of exposure. Although DNA fragmentation seen in Comet Assay can also be a consequence of excision and repair, rather than necessarily being irreversible final damage, authors suggest that cinnamaldehyde acts as an antimutagen through the enhancement of recombinational repair.…”
Section: Discussionmentioning
confidence: 85%
“…It was shown to reduce mutations in bacterial models (68,69), as well as prevent chemically or physically induced mutagenesis in human cells (70,71). Another benefit of this compound is its chemoprotective activities against inflammation and cancer.…”
Section: Phenolic Aldehydes Resulting From Lignin Hydrolysismentioning
confidence: 99%
“…Vanillin possesses potent antimutagenic properties, exemplified by its ability to reduce the extent of DNA lesions induced by several chemical mutagens (Ohta et al, 1986), UV light (Takahashi et al, 1990), as well as spontaneous mutations (Shaughnessy et al, 2006) in different Esherichia coli strains, mitomycin C-induced DNA lesions in (hybrid) Chinese hamster ovary cells (Sasaki et al, 1987;Gustafson et al, 2000), mouse bone marrow cells (Inouye et al, 1988), and somatic cells of Drosophila melanogaster (Santos et al, 1999), as well as X-ray-, UV light-, or H 2 O 2 -induced mutations in bone marrowderived cells Maurya et al, 2007) and hamster fibroblasts (V79 cells) Tamai et al, 1992) and hybrid ovary cells (Gustafson et al, 2000). In human mismatch repair-deficient (hMLH1 2 ) HCT116 colon cancer cells, vanillin decreased the number of spontaneous mutations in a concentrationdependent manner (19-73% at concentrations of 0.5--2.5 mM) (King et al, 2007). Vanillin also improved the efficacy of DNA damage repair mechanisms under conditions of oxidative stress (Maurya et al, 2007) and in spontaneously mutating colon cancer (HCT116) cells (King et al, 2007).…”
Section: B Pharmacokinetics and Pharmacodynamics Of Curcumin Catabolmentioning
confidence: 99%